An efficient and ecofriendly synthesis of highly functionalized pyridones via a one-pot three-component reaction. Issue 48 (30th July 2018) - Hosseini, Hajar; Bayat, Mohammad
Abstract : Synthesis of N -amino-3-cyano-2-pyridone derivatives in green solvent with simple procedure and high purity via a one-pot operation. Abstract : A simple and convenient protocol has been developed for the synthesis of N -amino-3-cyano-2-pyridone derivatives by a one-pot reaction of cyanoacetohydrazide, activated nitrile substrates (malononitrile, ethyl cyanoacetate, cyanoacetamide) and aromatic aldehydes in the presence of piperidine in water or a mixture of water and ethanol. The sequence of cascade reactions includes Knoevenagel condensation, Michael addition, intramolecular cyclization, imine-enamine tautomerization and oxidative aromatization. The main advantages of this procedure are availability of starting compounds, simple procedure, mild conditions, easy purification of products and the use of water or water/ethanol as green solvents.